2021
DOI: 10.1177/03400352211054113
|View full text |Cite
|
Sign up to set email alerts
|

The library as soft-power actor: A review

Abstract: This narrative review pursues an understanding of the relationship of libraries to the concepts of soft power and public and cultural diplomacy. The cross-disciplinary nature of the study required that the search approach include literature from both the International Relations and Library and Information Science disciplines. The analysed literature reveals three key gaps. First, research explicitly addressing the topic of ‘libraries and soft power’ is scarce. Second, the little Library and Information Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Libraries and international relations have been comprehensively studied in the fields of LIS and political science. Libraries have been linked to concepts and theories of library internationalism (Laugesen, 2019: 167; Lor, 2019: 58), cultural internationalism (Lor, 2019: 526; Witt, 2014a: 506, 2014b: 276), cultural diplomacy and foreign cultural relations (Cummings, 2003: 1, 3; Melissen, 2005: 21–22), public diplomacy (Cull, 2008: 9, 11; Maack, 2001: 59), soft power (Bell, 2022: 1458; Bell and Kennan, 2022: 707), the internationalization of LIS education, and the discourses around international librarianship and international partnerships (Carroll et al, 2001; Lee and Bolt, 2016; Lor, 2008, 2019; Mattson and Hickok, 2018). Most of the research data and researchers’ interests have mainly focused on the US context in the 20th century, with a qualitative focus on historical and textual studies, and few quantitative and theoretical studies (Mariano and Vårheim, 2021: 657).…”
Section: Libraries and Diplomacymentioning
confidence: 99%
See 1 more Smart Citation
“…Libraries and international relations have been comprehensively studied in the fields of LIS and political science. Libraries have been linked to concepts and theories of library internationalism (Laugesen, 2019: 167; Lor, 2019: 58), cultural internationalism (Lor, 2019: 526; Witt, 2014a: 506, 2014b: 276), cultural diplomacy and foreign cultural relations (Cummings, 2003: 1, 3; Melissen, 2005: 21–22), public diplomacy (Cull, 2008: 9, 11; Maack, 2001: 59), soft power (Bell, 2022: 1458; Bell and Kennan, 2022: 707), the internationalization of LIS education, and the discourses around international librarianship and international partnerships (Carroll et al, 2001; Lee and Bolt, 2016; Lor, 2008, 2019; Mattson and Hickok, 2018). Most of the research data and researchers’ interests have mainly focused on the US context in the 20th century, with a qualitative focus on historical and textual studies, and few quantitative and theoretical studies (Mariano and Vårheim, 2021: 657).…”
Section: Libraries and Diplomacymentioning
confidence: 99%
“…Library diplomacy, though not a new concept, has witnessed growing interest and discussion among scholars studying the role of soft power and cultural diplomacy in the field of library and information science (LIS; Bell and Kennan, 2022;Mariano, 2022;Mariano and Va ˚rheim, 2021). Library diplomacy is characterized by the role of library actors at individual, institutional, national and international levels in establishing international relations, influencing global policy decisions, and bridging understanding between and among various institutions and countries.…”
Section: Introductionmentioning
confidence: 99%
“…The research literature addressing the topic of "libraries and soft power" is limited, as indicated in literature reviews by Mariano and V arheim (2021) and Bell and Kennan (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research literature addressing the topic of “libraries and soft power” is limited, as indicated in literature reviews by Mariano and Vårheim (2021) and Bell and Kennan (2021). Most research literature on soft power and GLAM institutions addresses museums and cultural diplomacy (or museum diplomacy) (Cai, 2013; Davidson and Pérez-Castellanos, 2019; Flamini, 2014; Kong, 2015), and in some instances focuses on soft power attraction (Grincheva, 2014, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%